Quinoa Proteins (Chenopodium Quinoa Willd.) Fractionated by Ultrafiltration Using Ceramic Membranes: The Role of Ph on Physicochemical and Conformational Properties - Navarro-Lisboa, R; Matiacevich, S (Institution of Chemical Engineers, 2017)
Ultrafiltration is a technique used for the separation and recovery of proteins according to their molecular weight. The efficiency of the process can be controlled by control of the operational parameters, which can affect the structure and functionality of proteins in the final product. The aim of this study was to evaluate how the ultrafiltration process using ceramic membranes affects the physicochemical and conformational characteristics of quinoa protein fractions at two pHs above the isoelectric point of quinoa protein extracts. The results showed differences in permeate flux, reaching a volume concentration factor of three at 600 min at pH 7.0 and 300 min at pH 9.5. Thus, pH was a very important factor to control flux and membrane fouling. Higher protein concentration in the concentrate were detected at pH 9.5 (10.4 ± 0.2 mg/mL), whereas at pH 7.0, only 7.7 ± 0.1 mg/mL of recovered protein was obtained. In addition, differences in quinoa zeta potential and amino acid composition were found for the two pHs. The ultrafiltration process considerably affected the spatial configuration of the protein at pH 7.0, with a structured α-helix for the concentrate. The concentrates showed lower denaturation enthalpy values than the initial and permeate fractions at both pHs, indicating greater structural modification as result of ultrafiltration. In conclusion, pH is a critical variable affecting the physicochemical and conformational characteristics of ultrafiltrated quinoa proteins. It is important to evaluate the impact of the changes from ultrafiltration on functional properties for the development of novel food ingredients. © 2016 Institution of Chemical Engineers